Myotonic Disorders in an EMG Lab Over 12 Years - J Gordon Millichap (Pediatric Neurology Briefs, 2012)
Researchers at the EMG Laboratory, Boston Children's Hospital, MA assessed the spectrum of disorders associated with electrophysiologic myotonia in a pediatric electromyography laboratory.